(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Traumatic diaphragmatic injury is an uncommon but clinically important form of thoracoabdominal trauma. Diagnosis may be difficult, especially in blunt trauma, and delayed presentation can lead to diaphragmatic hernia and associated complications. Open surgery remains the standard treatment, but minimal access surgery is increasingly being introduced in selected stable patients. Aim: To study the clinical profile, injury pattern, operative management, and outcomes of diaphragmatic injury patients managed at a Level 1 Trauma Care Centre in Central India from 2023 to 2026, with emphasis on trends and the introduction of minimal access surgery. Materials and Methods: This retrospective observational study was conducted at a Level 1 Trauma Care Centre in Central India. All patients diagnosed with traumatic diaphragmatic injury and managed during the study period from 2023 to 2026 were included. Clinical records were reviewed for demographic details, mechanism of injury, timing of presentation, side of diaphragmatic injury, operative approach, use of minimal access surgery, postoperative complications, mortality, and hospital stay. Data were analysed using descriptive statistics. Results: A total of 13 patients were included in the study. The mean age was 39.5 ± 11.4 years, with a median age of 41 years and range of 18–55 years. All patients were males. Early presentation was observed in 10 patients (76.9%), while delayed presentation was seen in 3 patients (23.1%). Penetrating trauma was slightly more common than blunt trauma, accounting for 7 cases (53.8%) and 6 cases (46.2%), respectively. Left-sided diaphragmatic injury was predominant, being present in 12 patients (92.3%), while right-sided injury was seen in 1 patient (7.7%). All penetrating injuries presented early, whereas delayed presentation was observed only among blunt trauma patients. Open surgery was performed in 9 patients (69.2%). Minimal access surgery was attempted in 3 patients (23.1%), of whom 2 underwent completed laparoscopic/minimal access repair and 1 required subsequent open re-repair. Postoperative complications were documented in 4 patients (30.8%). Mortality was observed in 1 patient (7.7%). Among valid hospital-stay entries, the mean hospital stay was 13.9 ± 7.9 days, with a median of 14 days and range of 7–34 days. Conclusion: Traumatic diaphragmatic injury in this series predominantly affected adult males and was most commonly left-sided. Penetrating injuries presented early, while delayed presentation occurred only in blunt trauma, highlighting the need for high clinical suspicion in blunt thoracoabdominal injuries. Open surgery remained the mainstay of management; however, minimal access surgery was feasible in selected stable patients. Larger prospective studies are required to define the role and outcomes of minimal access surgery in diaphragmatic trauma.